Spondyloarthritis in familial Mediterranean fever: a cohort study - DURUÖZ, MEHMET TUNCAY (My University, 2022)
Familial Mediterranean fever (FMF) and spondyloarthritis (SpA) may show several common signs. This study aimed to evaluate the frequency of SpA and its manifestations in FMF, the impact of SpA on FMF, and the associations of non-episodic findings (heel enthesitis, protracted arthritis, and sacroiliitis) with the FMF features. Demographic, clinical, imaging, and genetic data were retrieved from medical records of the patients with adult FMF. To identify patients who met the classification criteria for SpA, data including rheumatologic inquiry were recorded. Patients with SpA and those who did not meet the criteria were compared in terms of FMF features. Regression analyses were performed to determine the factors that were most associated with sacroiliitis, enthesitis, and protracted arthritis. Of the 283 patients with FMF, 74 (26.1%) met the SpA criteria (64 axial, 10 peripheral); and 65 (22.9%) patients had sacroiliitis, 27 (9.5%) protracted arthritis, and 61 (21.6%) heel enthesitis. Patients with SpA were older and had more FMF severity, and heel pain rate than those without; however, genetic features, CRP, resistance to colchicine, and heel enthesitis did not differ. A meaningful number of patients without SpA had also displayed heel enthesitis, protracted arthritis, inflammatory back pain, heel pain, family history of SpA, and elevated CRP. Age was found to be the main predictor of heel enthesitis and protracted arthritis was linked with FMF severity. A significant number of patients with FMF meet the peripheral SpA classification criteria as well as axial SpA. SpA and its shared manifestations with FMF may have an impact on FMF.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Familial Mediterranean fever; Arthritis; Sacroiliitis; Enthesopathy; Spondylarthropathies; SOCIETY CLASSIFICATION CRITERIA; PROTRACTED ARTHRITIS; ENTHESOPATHY; VALIDATION; DIAGNOSIS; CHILDREN; PATIENT; TURKEY; PAIN